Numerical analysis of the strain values obtained by FBG embedded in a composite material using assumptions about uniaxial stress state of the optical fiber and capillary on the Bragg grating - Natalia Aleksandrovna Kosheleva; Valerii Matveenko; Grigorii Serovaev; Andrey Fedorov (Fracture and Structural Integrity)
One of the issues in the strain measurement with the help of fiber-optic sensors based on Bragg gratings is the calculation of the strain based on the information from the sensor and its correspondence to the material strain. Relationships between the data measured by the sensor and the strain in the Bragg grating have a unique solution under the condition of uniaxial stress state of the fiber, which are not fulfilled when the fiber is embedded in the material. The paper presents the results of numerical experiments with an example of a model problem for a polymer composite material with an embedded optical fiber, which can be surrounded by a resin pocket. The presented results allow to estimate the error of the strain values calculated on the basis of uniaxial stress state assumption of the optical fiber. Based on numerical calculations, parameters of a capillary on an optical fiber in the Bragg grating zone are estimated, ensuring uniaxial stress state of the fiber in the Bragg grating zone. To ensure these conditions, the cross section of the capillary in an isotropic material is a circle, and in an anisotropic material, good results can be obtained with an elliptical cross section.